SEJARAH DAN PERKEMBANGAN RETORIKA - . Rajiyem (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
This article is a compilation of rhetoric and its development toward public speaking. Rethoric is, logically and systematically regarded better than public speaking. Rhetoric can be emphasized on its art and message effectiveness. Rhetoric history started in Greek for political purposes to influence other people by using gimmick words and convincing expression and finally rhetoric is becoming a science. Further rhetoric development is the raise of modern rhetoric streams. Now, rhetoric becomes popular as public speaking.